Perforated duodenal ulcer associated with anterior abdominal abscess: A case report - Sun, Zhonghua; Al-naami, Awaji; Ali Khan, Liaqat (Australasian Medical Journal Pty Ltd, 2012)
Computed tomography (CT) has been regarded as the method of choice for detecting the presence, site and cause of gastrointestinal tract perforation. In addition to determining the presence of perforation, CT can also localise the perforation size and demonstrate direct and indirect findings relative to the perforation. In this case study, we report the CT results in a patient with perforated duodenal ulcer associated with anterior abdominal abscess, and highlight the diagnostic value of CT imaging.